IMPLEMENTATION OF COMPUTER TECHNOLOGY OPPORTUNITIES IN TEACHING FOREIGN LANGUAGES - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2023)
The article is about the relevance of the usage of information and communication technologies that makes it possible to solve the main contradiction of the modern education system - the contradiction between the rapid rate of increase in knowledge in the modern world and the limited possibilities of their assimilation by the individual. Now everyone understands that the Internet has colossal information capabilities and no less impressive services. But we must not forget that, no matter what properties this or that means of education, the information-subject environment possesses, didactic tasks, the features of the cognitive activity of students, due to certain goals of education, are primary. The Internet, with all its capabilities and resources, is one of the means of realizing these goals and objectives.